Upaya Peningkatan Pembelajaran Mengenal Unsur-Unsur Bangun Ruang Melalui Model Project Based Learning bagi Peserta Didik Autis - Febriyandi, Febriyandi; Nurhastuti, Nurhastuti; Agusta, Rini (Jurnal Penelitian Pendidikan Khusus, 2023)
This study raises the problem of autistic VII class at SLB N 1 Padang where the results of students' mathematics learning are still low in learning to recognize the elements of cubic and block geometric shapes. The purpose of this study was to see the process of implementing learning to recognize geometric elements and to improve learning outcomes for class VII autistic students with material to recognize geometric elements of cubes and blocks through a project based learning model. The method used in this research is classroom action research which consists of two cycles, where each cycle has four stages, namely planning, implementing, observing and reflecting. based on the results of the study, students experienced an increase in the learning process, it was seen that children were more independent and the results of learning material about geometric elements increased after using the project based learning model. This proves that the project based learning model can improve learning outcomes for class VII autistic students as seen from the learning outcomes of autistic students which increase each cycle.